A case study on the role of the Jewish Lobby in the US-Israel relations during the Yom Kippur War - Cordero, Christina Victoria O. (Animo Repository, 2005)
This study links together several ideas, such as: the Jewish diaspora and the American Jews, the role of the Jewish lobby in American politics, foreign policy making and the Yom Kippur War. This study asserts that the US-Israel relation is triangular, with the Jewish lobby as the medium of Israel in articulating their intentions. It presents how the Jewish lobby is instrumental in the US-Israel relation. Since the study is set in the context of the Yom Kippur War and the three years prior to that, it will also be able to show the importance of Israel in the Cold War that existed between the United States and the Soviet Union.